A New Topology of Cross-Switched Multilevel Inverter - Jefry, Nur Atiqah Binti (Curtin University, 2022)
This study proposed a Multilevel Inverter (MLI) topology that generates a high number of output voltage levels with a reduced number of components. The proposed topology was configured with symmetrical, asymmetrical, and hybrid configurations. Each configuration generates a different level of output voltage. In parallel to the increased output level, the output voltage has a better output quality (i.e., a lower percentage of total harmonic distortion), simple design and less demanding operation.